DISSOLUTION OF MARRIAGE: FUNCTIONAL APPROACH TO POLISH-ENGLISH TRANSLATION OF SELECTED COURT DOCUMENTS - JUSZKIEWICZ, Hanna (Comparative Legilinguistics, 2012)
The paper presents results of a study aimed at analysing problems that arise in Polish‑English translation of selected court documents in divorce and judicial separation cases, as well as the ways of solving such problems in the light of the functional approach to translation. The methodology used includes parallel texts analysis, corpus linguistics for term extraction and comparative legal research into concept comparison. The results, including comments on specific terminological, phraseological and textual choices and a critical analysis of certain established equivalents, are presented in the form of an annotated translation. The findings also include general observations on the types and the sources of common problems encountered by both beginner and experienced translators. Finally, a need is identified for developing a more effective form of presenting results of practice-oriented research in the field of translation studies, especially with reference to legal translation, which would account for a richer knowledge component and more extensive contextual information than traditional dictionaries and term‑bases.